2009
DOI: 10.1159/000218330
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an Extracorporeal Endotoxin Adsorber System during Hyperdynamic Porcine Endotoxemia

Abstract: Background: Endotoxemia is a crucial factor in the pathogenesis of sepsis. Elimination of endotoxin is aimed at the reduction of sepsis-related morbidity and lethality. The objective of this study was to examine the impact of an endotoxin adsorber on hemodynamics, O2 exchange and metabolism during resuscitated porcine endotoxemia. Methods: Twenty pigs were randomized into 2 intervention groups (n = 7 each) and 1 control group (n = 6). Endotoxemia was induced by continuous intravenous application of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…The capacity of albumin to bind endotoxin could also be an explanation for the effect seen with MARS therapy [148]. It remains unclear whether it will ever be possible to use this interesting strategy in patients, since preclinical data are not yet convincing [151].…”
Section: Experimental Strategiesmentioning
confidence: 99%
“…The capacity of albumin to bind endotoxin could also be an explanation for the effect seen with MARS therapy [148]. It remains unclear whether it will ever be possible to use this interesting strategy in patients, since preclinical data are not yet convincing [151].…”
Section: Experimental Strategiesmentioning
confidence: 99%
“…In the only large animal study available so far, Bracht et al [34] examined the impact of an extracorporeal endotoxin adsorber on hemodynamics, O 2 exchange, and metabolism during resuscitated porcine endotoxemia. Pigs were randomized for intravenous continuous application of LPS of E. coli O111:B4 (0.1 μg h −1 kg −1 ) for 8 h or sham.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…It was concluded that despite typical clinical signs of endotoxemia, the adsorber system had no significant effect on hemodynamic, metabolic, and acid-base parameters during endotoxic shock. The reasons for the absence of an effect were elusive; however, failure of the method per se or exceeded capacity of the adsorber could not be excluded [34].…”
Section: Animal Experimentsmentioning
confidence: 99%
“…7,8 In this treatment strategy of hemoperfusion, circulating endotoxin and immune mediators in blood are removed by a selective adsorber. [9][10][11][12] The adsorber Toraymyxin was developed by Toray Industries Inc. based on polymyxin B-immobilized polystyrene fabric, and has been applied to sepsis patients as a blood purication medical device in Japan. 13,14 In the late 2000s, over 30 000 patients received Toraymyxin treatment and positive results were achieved.…”
Section: Introductionmentioning
confidence: 99%